Cost-Effectiveness of Health Care Interventions to Address Intimate Partner Violence: What Do We Know and What Else Should We Look for? - Gold, L.; Norman, Richard; Devine, A.; Feder, G.; Taft, A.; Hegarty, K. (Sage Publications, Inc., 2011)
Intimate partner violence (IPV) creates a substantial burden of disease and significant costs to families, communities, and governments. Building the evidence for effective interventions to reduce violence and its sequelae requires increased use of economic evaluation to inform policy through the analysis of costs and potential savings of interventions. The authors review existing economic evaluations and present case studies of current research from the United Kingdom and Australia to illustrate the strengths and limitations of two approaches to generating economic evidence: economic evaluation alongside randomized controlled trials and economic modeling. Economic evaluation should always be considered in the design of IPV intervention research.